Pengaruh Perlakuan Awal Hidrolisis Ampas Sorgum (Sorghum Bicolor L.) Terhadap Fermentasi Untuk Produksi Bioetanol Sebagai Energi Terbarukan - Sefrinus Maria Dolfi Kolo; Stevanny Yulia Margarita Nggai; Yuni Sine (Department of Chemistry, Faculty of Science and Technology UIN Maulana Malik Ibrahim Malan, 2022)
Bioethanol has been successfully produced from sorghum (Sorghum bicolor L.) seed dregs as a biofuel to replace fossil fuels. The goal of this study is to find out what sulfuric acid concentration produces sugar content during hydrolysis utilizing microwave and an autoclave. The concentrations of sulfuric acid used in this experiment were 0.5, 1, 2, and 5%. The hydrolysis of sorghum brans is suspended with a sulfuric acid solution, then in the hydrolysis using microwave (temperature 150°C for 30 minutes) and autoclave (pressurized 1 atm temperature 121 °C for 30 minutes). The fermentation using yeast saccharomyces cerevisiae for 5 days. The analyzed through reducing sugar content using UV-VIS, then morphology of sorghum brans using SEM, the density of ethanol using pycnometer, and analysis ethanol levels using GC. The analysis used SEM is sulfuric acid was able to damage the surface structure of sorghum brans. Produced the optimum reducing glucose occurred in hydrolysis using a microwave with a sulfuric acid concentration of 1% is 44,97 gr/L, then using methods autoclave produced the optimum glucose reducing with a sulfuric acid concentration of 5 % is 30,86 g/L. The analysis ethanol used pycnometer is 1,96%. and gas chromatography converting of ethanol was 15.76%.